Design of high‐efficiency microwave wireless power transmission system. Issue 7 (23rd April 2016) - Ma, Haihong; Li, Xi; Sun, Linlin; Xu, Hui; Yang, Lin
ABSTRACT: Microwave wireless power transmission (MWPT) is a new‐style transmission mode, which has wide application on Space Solar Power Station (SSPS), Payload Spacecraft Module, high power weapon, and so on. Based on the requirement of space application, one MWPT system has been presented. The solid source provides microwave power. The diameter of transmitting paraboloid antenna is 2.4 m. The receiving antenna is an array rectenna, with the scale of 2.4 m*2.4 m. The transmission distance is 11 m. And the DC‐to‐DC transmission efficiency is better than 16.5%, which is admirably agreed with the estimation results. The experimental results could promote the theory study‐engineering application conversion of MWPT technique. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1704–1707, 2016